Pendampingan eksplorasi potensi diri melalui asesmen minat dan bakat di lingkungan SMK Kota Tasikmalaya - Siti Fatimah; Alawiyah, Tuti; Rismawati Siddik, Riesa (Abdimas Siliwangi, 2024)
The development of interests and talents for students in vocational schools is an important aspect of career guidance which aims to help identify personal potential, interests, talents and abilities in academic and non-academic fields. The main aim of this service is to facilitate students to explore their potential by carrying out self-development through training activities, seminars, workshops and mentoring carried out by lecturers in the Guidance and Counseling Study Program, Faculty of Education, IKIP Siliwangi. This activity involved 260 students of class XII Vocational High School (SMK) Al-Basith and Al-Khoeriyah, Tasikmalaya City. The results of this service are expected to provide benefits for students and guidance and counseling teachers in supporting the development of students' potential; increase learning motivation; have a better understanding of his interests and talents; can make subject choices that suit future career goals; develop the skills, knowledge and attitudes needed to face challenges at higher levels of education or the world of work; and be more ready to make the right decisions regarding further studies or work that suits their interests so that they become more responsible for their career choices.